Assessment of the genetic variation of Malaysian durian varieties using inter-simple sequence repeat markers and chloroplast DNA sequences - Siew, Ging Yang; Ng, Wei Lun; Salleh, Muhammad Fadzly; Tan, Sheau Wei; Ky, Huynh; Mohammed Alitheen, Noorjahan Banu; Tan, Soon Guan; Yeap, Swee Keong (Universiti Putra Malaysia Press, 2018)
To date, 124 durian varieties have been registered with the Malaysian Department of Agriculture based on phenotypic characteristics. However, the levels and patterns of genetic variation among the varieties are still unknown. In this study, the leaves of 27 durian varieties were sampled from four durian orchards in Universiti Putra Malaysia, namely Bukit Ekspo, Putra Mart, Ladang Puchong and Ladang 5. Twenty five inter-simple sequence repeat (ISSR) primers were tested for PCR amplification on DNA samples. Twelve ISSR primers amplified 133 clear and reproducible DNA fragments and 122 (91.73%) were polymorphic, indicating a high level of genetic variation among these durian varieties. Primers flanking four chloroplast DNA (cpDNA) regions (trnL-trnF, atpB-rbcL and trnH-psbA intergenic spacers as well as the partial matK gene) were tested for PCR amplification. Two cpDNA regions (trnL-trnF and matK) were successfully amplified, but showed no variation in their DNA sequences, even when additional samples from Vietnam were included. The findings in this preliminary study lay a foundation for more comprehensive future studies on the genetic variation among durian varieties.